The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0186148
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spinal canal MRI diameter is smaller in herniated disc cauda equina syndrome patients

Abstract: IntroductionCorrelation between magnetic resonance imaging (MRI) and clinical features in cauda equina syndrome (CES) is unknown; nor is known whether there are differences in MRI spinal canal size between lumbar herniated disc patients with CES versus lumbar herniated discs patients without CES, operated for sciatica. The aims of this study are 1) evaluating the association of MRI features with clinical presentation and outcome of CES and 2) comparing lumbar spinal canal diameters of lumbar herniated disc pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…[7] Korse et al also reported statistically significant differences in the normal spinal canal diameters between patients with versus those without CES. [6] However, we found greater canal narrowing form Group B versus Group A patients at the L4-L5 and L5-S1 levels; the lesser canal sizes in Group B patients at L4-L5 and L5-S1 explained the occurrence of CES despite a lesser mean percentage of compression due to IDH versus the higher lumbar levels.…”
Section: Discussioncontrasting
confidence: 53%
“…[7] Korse et al also reported statistically significant differences in the normal spinal canal diameters between patients with versus those without CES. [6] However, we found greater canal narrowing form Group B versus Group A patients at the L4-L5 and L5-S1 levels; the lesser canal sizes in Group B patients at L4-L5 and L5-S1 explained the occurrence of CES despite a lesser mean percentage of compression due to IDH versus the higher lumbar levels.…”
Section: Discussioncontrasting
confidence: 53%
“…Kim et al have demonstrated that a longer walking distance is associated with a larger dural sac CSA [9]. Korse et al have found that patients with cauda equina syndrome due to lumbar disc herniation have significant smaller anteroposterior spinal canal diameters in the lumbar lesion than patients with lumbar disc herniation without cauda equina syndrome [17]. Yoshiiwa et al have reported that hypertrophy of ligamentum flavum development is associated with severe disc degeneration, segmental instability, and severe facet joint osteoarthritis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Further, patients with sciatica and a CES due to a lumbar herniated disc have a significantly smaller epidural space than sciatica patients without CES [24]. Since 1-10% of patients with a known lumbar herniated disc develop CES [24], the chances that an interventional procedure is performed during the time-frame of this natural neurological progression is realistic, thereby obscuring the causal relation with the epidural corticosteroid injection. In patients with spinal stenosis, injection of a small volume is recommended to minimize a possible pressure increase in the epidural space.…”
Section: Contributing Factors To Cauda Equine Syndromementioning
confidence: 99%